2012
DOI: 10.1093/cercor/bhs270
|View full text |Cite
|
Sign up to set email alerts
|

A Weighted and Directed Interareal Connectivity Matrix for Macaque Cerebral Cortex

Abstract: Retrograde tracer injections in 29 of the 91 areas of the macaque cerebral cortex revealed 1,615 interareal pathways, a third of which have not previously been reported. A weight index (extrinsic fraction of labeled neurons [FLNe]) was determined for each area-to-area pathway. Newly found projections were weaker on average compared with the known projections; nevertheless, the 2 sets of pathways had extensively overlapping weight distributions. Repeat injections across individuals revealed modest FLNe variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

81
1,276
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 817 publications
(1,362 citation statements)
references
References 110 publications
81
1,276
5
Order By: Relevance
“…Vincent et al (2007) showed qualitatively that functional connectivity in the anesthetized macaque correlated well with anatomical connectivity when testing a seed region in the vicinity of area LIPv, whereas a seed region centered in area V1 revealed evidence of a combination of direct connections (e.g., with area MT) and indirect connections (e.g., with the horizontal meridian of contralateral area V1, which has no direct interhemispheric connections). A recent study showed a modest (r ¼ 0.35) but highly significant correlation between functional connectivity in the anesthetized macaque and the Markov et al (2012) quantitative parcellated connectivity matrix (Miranda-Dominguez et al 2014). Importantly, the analysis revealed many false negatives (negative functional connectivity, or anti-correlation between areas that are strongly connected anatomically).…”
Section: Functional Connectivity Validation In the Macaquementioning
confidence: 96%
See 1 more Smart Citation
“…Vincent et al (2007) showed qualitatively that functional connectivity in the anesthetized macaque correlated well with anatomical connectivity when testing a seed region in the vicinity of area LIPv, whereas a seed region centered in area V1 revealed evidence of a combination of direct connections (e.g., with area MT) and indirect connections (e.g., with the horizontal meridian of contralateral area V1, which has no direct interhemispheric connections). A recent study showed a modest (r ¼ 0.35) but highly significant correlation between functional connectivity in the anesthetized macaque and the Markov et al (2012) quantitative parcellated connectivity matrix (Miranda-Dominguez et al 2014). Importantly, the analysis revealed many false negatives (negative functional connectivity, or anti-correlation between areas that are strongly connected anatomically).…”
Section: Functional Connectivity Validation In the Macaquementioning
confidence: 96%
“…Major progress on this front has come from a recent systematic effort from the laboratory of Henry Kennedy, revealing that connectivity profiles are more highly distributed and that connection strengths span a much wider range than previously realized (Knoblauch et al 2015). Using a 91-area cortical parcellation and retrograde tracers injected into 29 cortical areas, Markov et al (2012) determined that each cortical area receives on average inputs from 55 other areas out of a (minimum) 26 and (maximum) 87; when expressed as the fraction of retrogradely labeled neurons, these pathways vary over five orders of magnitude in connection strength (Markov et al 2011(Markov et al , 2012Knoblauch et al 2015). This translates to 1615 inter-areal pathways out of 2610 possible in a 29 Â 91 connectivity matrix.…”
Section: Distributed Cortical Connectivitymentioning
confidence: 99%
“…While processing hierarchies are typically described in sensorimotor systems (e.g., [9,10]), they have been proposed to extend to transmodal association areas [8,44,45]. In support of this view, spatial gradients of functional integration ranging from unimodal to transmodal areas have recently been described in the human cortex [35,46].…”
Section: Functional Processing Hierarchiesmentioning
confidence: 99%
“…The location of an area among its neighbors thus provides insight into its microstructural characteristics [6], its connections to other parts of the brain [7], and eventually its position in global processing hierarchies [8]. Consider, for example, the well-researched visual system of the macaque monkey [9,10]. Along the visual hierarchy, low-level visual features are increasingly abstracted and integrated with information from other systems.…”
mentioning
confidence: 99%
“…Numerous new (and mostly relatively weak) projections were uncovered, and the overall connectivity profile for each area was best approximated by a lognormal distribution (Markov et al 2011), with a few strong projections and a large admixture of medium or weak pathways. Graph analysis provided evidence for a relatively high proportion of unidirectional links (Markov et al 2014), a strong contribution of long-distance projections towards areal specificity (Markov et al 2013a), significant distance-dependence of connection densities (Ercsey-Ravasz et al 2013), and hierarchical arrangement of areas into "counter-streams" (Markov et al 2013b). Several of these characteristic topological features are also found in other mammalian species, e.g., the cat or rodent brain.…”
Section: Macroscalementioning
confidence: 84%